Effektivitas Komite Audit, Dewan Komisaris Independen dan Biaya Audit - Nurjanah, Fitri; Imam Amrozi, Akhmad (E-Jurnal Akuntansi; Vol 31 No 3 (2021), 2021)
The purpose of this study is to analyze the effect of effectiveness of audit committee and independence board of commissioner on audit fee. This research uses samples of Non-financial companies in Indonesia Stock Exchange (IDX) in 2015-2018. The sampling technique used purposive sampling. The total number of companies used as research samples is 584 companies. Using tools SPSS 20 and testing hypothesis using linear regression. The F test indicates a stable and significant model. R square is 49,4%The result show independence board of commissioner and Effectiveness of audit committee can positively significant effect on audit fee because board of commissioners and audit committee wants a higher audit quality from the auditor. Keywords: Board Of Commissioners; Effectiveness Of Audit Committee; Audit Fee.